2011
DOI: 10.1371/journal.pcbi.1002096
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of the Protein-Protein Interactions between Human BRCA2 BRC Repeats and RAD51 Reveals Atomistic Determinants of Affinity

Abstract: The breast cancer suppressor BRCA2 controls the recombinase RAD51 in the reactions that mediate homologous DNA recombination, an essential cellular process required for the error-free repair of DNA double-stranded breaks. The primary mode of interaction between BRCA2 and RAD51 is through the BRC repeats, which are ∼35 residue peptide motifs that interact directly with RAD51 in vitro. Human BRCA2, like its mammalian orthologues, contains 8 BRC repeats whose sequence and spacing are evolutionarily conserved. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…Different meta-analysis and studies on RAD51 have earlier shown an association of this polymorphism with an elevated breast cancer risk (Cole et al, 2011;Falvo et al, 2011;Gao et al, 2011;Hosseini et al, 2012). The RAD51 135G/C polymorphism located in the 5' untranslated region seems to be of functional relevance.…”
Section: Discussionmentioning
confidence: 92%
“…Different meta-analysis and studies on RAD51 have earlier shown an association of this polymorphism with an elevated breast cancer risk (Cole et al, 2011;Falvo et al, 2011;Gao et al, 2011;Hosseini et al, 2012). The RAD51 135G/C polymorphism located in the 5' untranslated region seems to be of functional relevance.…”
Section: Discussionmentioning
confidence: 92%
“…Both negative (22,55–57) and positive (19,58) effects have been reported. Our experimental conditions were more similar to those reported in (57,59), in that we used a synthesized peptide, whereas Carreira and colleagues used Glutathione S-transferase-fused BRC4. Similar to (22,55–57), we observed destabilization of the extended RAD51 nucleoprotein filament.…”
Section: Resultsmentioning
confidence: 99%
“…This allows an accurate QM description of systems of thousands of atoms [5], including entire proteins [14,29,30]. The ONETEP formalism is based on a reformulation of conventional Kohn-Sham DFT [1,2] in terms of the single-particle density matrix…”
Section: Methodsmentioning
confidence: 99%